Evaluation of the Thermal Insulation Potential of Post-Harvest Blocks Using the Native Strain of the Edible Mushroom Pleurotus ostreatus - Miguel Aravena; Leonardo Almonacid-Muñoz; Carlos Rojas-Herrera; Héctor Herrera; Juan Pablo Cárdenas-Ramírez; Alejandro Veliz Reyes; Cristiane Sagredo-Saez (Buildings)
In recent years, the need to adopt materials that are partially or fully recyclable or biodegradable has grown significantly. This paper presents a study aiming to develop a physical and thermal characterization of post-harvest blocks (spent mushroom substrate) used in the production of the edible mushroom Pleurotus ostreatus in order to test its feasibility as an insulation material. For this purpose, culture blocks based on wheat straw residues were prepared using a wild strain of the fungus. After the mushroom harvest, the post-harvest blocks were evaluated for stability, thermal conductivity, moisture content, fire behavior, and surface analysis. The results showed that the post-harvest blocks had an average thermal conductivity of 0.032 W/mK, a density of 56.63 kg/m3, and a moisture content of 5.96%. They also exhibited high fire resistance. The culture blocks showed stable dimensional properties, reasonable productivity, low moisture, high density, and fire resistance. Therefore, results suggest that this material could be used as insulation in construction.